A strong, ultrastretchable, antifreezing and high sensitive strain sensor based on ionic conductive fiber reinforced organohydrogel. (15th August 2022) - Wang, Di; Zhang, Jin; Fan, Chonghui; Xing, Jian; Wei, Anfang; Xu, Wenzheng; Feng, Quan; Wei, Qufu
Abstract: Strain sensors based on ionic conductive hydrogels are highly appreciated for their intrinsic biocompatibility, flexibility as well as soft characteristics. However, simultaneous realization of excellent mechanical properties, ionic conductivity, and low-temperature tolerance remains a grand challenge. Herein, we developed a novel fiber reinforced organohydrogel through facilely combining the polyacrylamide grafted gelatin (PAM/GE) hydrogel with polyurethane (PU) electrospun fiber membrane in glycerol-water binary solvent system. The fiber reinforced organohydrogel exhibited intriguing integrated characteristics, including outstanding mechanical performance (stress up to 3.09 MPa, strain up to 614%), freeze tolerance (−40 °C) and high ionic conductive (1.51 S m −1 ) at room temperature, attributed to the synergistic effects of PU electrospun fiber membrane and PAM/GE hydrogel. It is worth mentioning that, the presence of glycerol and NaCl endowed the fiber reinforced organohydrogel with outstanding ionic conductivity (0.89 S m −1 ) even at −40 °C, allowing for practical applications in harsh conditions. When exploited as a wearable strain sensor, the as-prepared fiber reinforced organohydrogel showed excellent sensitivity, stability and repeatability for the detection of human motions. This work provides new insights into design of strong, stretchable, and freezing-tolerant ionic conductive hydrogels, paving the way to developing multifunctional sensors. Highlights: The fiber reinforced organohydrogel was prepared through organhydrogel filled electrospun fiber membrane. The glycerol-water binary solvent system was introduced to endow fiber reinforced organohydrogel good antifreeze property. The polyurethane electrospun fiber membrane was introduced to improve the tensile strength and elasticity of organohydrogel observably. As a strain sensor, the fiber reinforced organohydrogel shows high strain sensitivity, good stability and repeatability.